2018
DOI: 10.1021/acssuschemeng.7b04556
|View full text |Cite
|
Sign up to set email alerts
|

An Insight of Synergy between Pseudomonas aeruginosa and Klebsiella variicola in a Microbial Fuel Cell

Abstract: The interspecies interactions in microbial communities are very complex, rendering identification of synergistic or antagonistic relationships very difficult; however, understanding the mutualistic relationship between the microbes is exigent to gain deeper insight into their performance in wastewater fed microbial fuel cells (MFCs). In the present study, we aimed to explore the ecological networks between the microorganisms in a defined coculture system comprising with Pseudomonas aeruginosa (P. aeruginosa) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 44 publications
1
41
0
Order By: Relevance
“…After optimization of oxygen supply, 400% enhancement of current production was observed [94]. The defined co-culture system of P. aeruginosa and Klebsiella variicola was more efficient than either of these two strains alone, and the maximum current density was about 3 times higher [95]. Further optimization of the process parameters by response surface methodology led to a maximum power density of 12.88 W/m 3 [96].…”
Section: Mixed Communities As Electricigens In the Anodementioning
confidence: 99%
“…After optimization of oxygen supply, 400% enhancement of current production was observed [94]. The defined co-culture system of P. aeruginosa and Klebsiella variicola was more efficient than either of these two strains alone, and the maximum current density was about 3 times higher [95]. Further optimization of the process parameters by response surface methodology led to a maximum power density of 12.88 W/m 3 [96].…”
Section: Mixed Communities As Electricigens In the Anodementioning
confidence: 99%
“…This would also minimise the power required for sparging the anode with N 2 gas. Previous studies have demonstrated the syntrophic relation of P. aeruginosa in co-cultures to be based on metabolite-based mutualism [ 36 , 37 ]. The combined respiration of E. coli and P. aeruginosa in the co-culture resulted in improved biofilm formation and substrate utilization (Figures 3 and 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…The charge transfer resistances Rct1 was found slightly lower than the Rct2 indicating a fast charge transfer between the yeast cells at biofilm as the electrode (ter Heijne et al, 2018). The mass transfer resistance was found to be significantly higher compared to the other resistances indicating poor diffusivity might be due to the higher diffusion path (M Amirul Islam, Ethiraj, Cheng, Yousuf, & Khan, 2018). Further study should be done to reduce the mass transfer resistance in the MFC for the enhancement in the power generation.…”
Section: Eis Analysismentioning
confidence: 92%